War bows longbow, crossbow, composite bow and Japanese yumi - Loades, Mike 1950- (Osprey Publishing, 2019)
Introduction -- Chapter one: the longbow. Development: the longbow's genesis and production ; Use: at full draw ; Impact: assessing the longbow -- Chapter two: the crossbow. Development: lock, stock and lath ; Use: steady, steady, steady: shoot ; Impact: bolts from the blue -- Chapter three: the composite bow. Development: engineering the optimal bow ; Use: archery -- a very martial art ; Impact: different bows for different blows -- Chapter four: the Japanese yumi. Development: the asymmetric bow ; Use: the way of the bow and the horse ; Impact: the sting of the samurai -- Epilogue.